1994
DOI: 10.1037/0882-7974.9.1.149
|View full text |Cite
|
Sign up to set email alerts
|

Memory for facts, source, and context: Can frontal lobe dysfunction explain age-related differences?

Abstract: Age-related differences in memory for facts, source, and contextual details were examined in healthy young (18-35 years old) and old (65-80 years old) volunteers. In all tested memory functions, decline over time was greater in the elderly than in the young. A time-dependent increase in the prevalence of source amnesia errors was clearly associated with old age. Contrary to several recent reports, measures of frontal lobe functions did not predict source memory. Nevertheless, some of these putative frontal fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
69
1
5

Year Published

1997
1997
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(81 citation statements)
references
References 47 publications
6
69
1
5
Order By: Relevance
“…Source memory was significantly poorer in older adults than in young adults, consistent with previous research (Brown et al, 1995;Ferguson et al, 1992;Henkel et al, 1998;McIntyre & Craik, 1987;Schacter et al, 1991;Spencer & Raz, 1994;Trott et al, 1997; for reviews, see Prull et al, 2000;Spencer & Raz, 1995). One possibility that we examined was that emotion would cause an item-source trade-off in older adults' memory, as has previously been found in some studies (e.g., Naveh-Benjamin & Craik, 1996; for a possible example in young adults, see Jurica & Shimamura, 1999).…”
Section: Aging and Source Memorysupporting
confidence: 81%
“…Source memory was significantly poorer in older adults than in young adults, consistent with previous research (Brown et al, 1995;Ferguson et al, 1992;Henkel et al, 1998;McIntyre & Craik, 1987;Schacter et al, 1991;Spencer & Raz, 1994;Trott et al, 1997; for reviews, see Prull et al, 2000;Spencer & Raz, 1995). One possibility that we examined was that emotion would cause an item-source trade-off in older adults' memory, as has previously been found in some studies (e.g., Naveh-Benjamin & Craik, 1996; for a possible example in young adults, see Jurica & Shimamura, 1999).…”
Section: Aging and Source Memorysupporting
confidence: 81%
“…Craik et al 1990) and sometimes it is not (e.g. Johnson et al 1995;Spencer & Raz 1994). Johnson et al (1995) suggested that such inconsistencies in outcomes may not be surprising given the variety of qualitative characteristics and processes potentially involved in source memory and the lack of speci¢city of neuropsychological tests of frontal function.…”
Section: (C) Ageing and Source Monitoringmentioning
confidence: 99%
“…Because age differences in source memory appear to become more exaggerated over time (Brown et al, 1995;Mclntyre & Craik, 1987;Schacter et al, 1991;Spencer & Raz, 1994), another group of older adults was tested with a 2-day retention interval. 2 Thus, the effects of similarity on source discriminability could be compared between younger and older adults when their recognition levels were equivalent and when their retention intervals were equivalent.…”
Section: The Source Monitoring Framework and Agingmentioning
confidence: 99%